Reperfusion after pulmonary embolism - long-term follow-up, risk factors, clinical impact - Mrozek, Jan; Petrova, Jana; Vaclavkova, Jana; Janovsky, Vladimir; Kraus, Lubos; Jansa, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
BACKGROUND AND AIM: Thromboembolic disease is the third most common cardiovascular disorder and deep vein thrombosis carries the risk of pulmonary embolism (PE). Questions related to reperfusion after PE remain, especially risk factors. Incomplete reperfusion after PE is closely related to the development of chronic thromboembolic pulmonary hypertension. The aim of this study was to determine the relation between reperfusion after PE in the long term over a period of 24 months, laboratory results and clinical risk factors found during the initial PE event. PATIENTS AND METHODS: 85 consecutive patients with a first episode of acute PE, diagnosed at 4 cardiology clinics, were followed up using clinical evaluation, scintigraphy and echocardiography (6, 12 and 24 months after the PE. 35 patients were in the low risk category (41%), 42 (49%) in the intermediate risk group and 8 (9%) in the high risk category. RESULTS: Perfusion defects persisted in 20 patients (26%) after 6 months, in 19 patients (25%) after 12 months and in 14 patients (19%) after 24 months. The incidence was more frequent in older patients, with more serious (higher risk) PE, increased right ventricular internal diameter during the initial episode, and more significant tricuspid insufficiency in the initial echocardiography. Notably, higher hemoglobin levels were also shown as a significant risk factor. The presence of perfusion defects after 24 months correlated with a concurrent higher pulmonary pressure but not with either patient function or adverse events (recurrence of PE, re-hospitalization or bleeding). In 3 cases (4% of patients), long-term echocardiographic evidence of pulmonary hypertension was detected. CONCLUSION: Even after 24 months from acute PE with adequate anticoagulation treatment, incomplete reperfusion was found in 19% of patients with a corresponding risk of chronic thromboembolic pulmonary disease and hypertension.
Keywords: senioři; incomplete reperfusion; Pulmonary Embolism; Perfusion Imaging; echokardiografie; reperfuze; plicní embolie; Echocardiography; Middle Aged; Thrombolytic Therapy; mužské pohlaví; Multimodal Imaging; Adult; mladý dospělý; Prospective Studies; Follow-Up Studies; následné studie; pulmonary embolism; Young Adult; antikoagulancia; ženské pohlaví; perfuzní zobrazování; Humans; prospektivní studie; Anticoagulants; CT angiografie; lidé středního věku; Computed Tomography Angiography; rizikové faktory; multimodální zobrazování; trombolytická terapie; risk factor; dospělí; Female; Aged; Reperfusion; Risk Factors; lidé; Male